A study on evaluation of probable sources of heavy metal pollution in groundwater of Kalpakkam region, South India - Chidambaram, S.; Karmegam, U.; Prasanna, Mohan; Sasidhar, P. (Springer US, 2012)
This study investigates the heavy metal pollution vulnerability of the groundwater in the coastal aquifers of Kalpakkam region in the state of Tamilnadu, India. Integrated-approach includes pollution evaluation indices, principal component analysis (PCA), and correlation matrix (CM) to evaluate the intensity and source of pollution in groundwater. The data have been used for the calculation of heavy metal pollution index (HPI) and degree of contamination (C d). The mean metal levels in groundwater followed a descending order as: Zn > Ba > Fe > Al > Se > Mn > Cu > Ni > Pb > Cr > Mo > As > Cd > Sb > Be. The concentrations of Fe, Cd, Zn, Se, Ba, Mn, Ni, Pb, and Al in some of the groundwater samples exceed the maximum admissible concentration (MAC). The HPI and C d yield different results despite significant correlations between them. The following elemental associations were obtained from PCA and CM: Fe–Mn–Ni–Cr–Pb–Cd–Zn–Be–Al, Cu–As, Sb–As, Al–Ba and Se–Mo, which could be linked to anthropogenic sources (i.e., processes of tannery and dying industries with some contribution from the landfill leachate and municipal sewage). GIS-based factor score maps suggest that the activities of tannery industries and landfill leachate are pervasive processes in the area. This study has provided the evidence that effluents discharged from the tannery and auxiliary industries and landfill leachate are the main sources of heavy metal pollution in the groundwater. The high metal concentrations observed in the groundwater may have serious public health and potential environmental hazard implications.